White mule - Williams, William Carlos . (Penguin Books., 1965)
White Mule is the first of a trilogy of novels by William Carlos Williams about the immigrant Stecher family in New York at the turn of the 20th century. The "White Mule" of the title refers to Flossie, the angry, assertive, uncompromising baby, who can kick like White Mule whiskey